Evaluating the effect of white vinegar on candida albicans colonies in complete acrylic dentures An invitro study - قرحيلي, غدير; محمود محمود (Latakia University Journal -Medical Sciences Series, 2024)
Objective:This study evaluated the effectiveness of white vinegar on candida albicans colonies in complete acrylic dentures comparing the effect of hypochlorite de sodium soaking method، Methods:smears were collected from the dentures fitting surface of 20 patients with denture stomatitis to determine the candida albicans only subjects with positive results were included and randomly divided into two experimental groups of 10 subjects each: Group 1: patients had their maxillary complete dentures soaked in white vinegar 4% for 3 hours. Group 2: patients had their maxillary complete dentures soaked in hypochlorite de sodium 1% for 10 min. Swab samples were taken from two different areas before and after treatment، and then plated on a selective media for candida species. After incubation(48 h \ 37C) the number of colony forming units. Results: soaking in white vinegar 4% for 3 h resulted in sterilization of all dentures evaluated.soaking in hypochlorite de sodium 1% for 10 min resulted in a significant decrease in colony forming units of candida after treatment in comparison obtained before treatment. Conclusion: soaking in white vinegar 4% for 3 h was effective in sterilization of all tested dentures therefore it may be a potential Method to prevent or treat denture stomatitis or to prevent cross-contamination between dental office and laboratory.